Deep Trenches Cleanliness Challenges for CMOS Image Sensors. (15th August 2017) - Garnier, Philippe; Dignat, Franck; De Buttet, Côme
Abstract : Selective silicon nitride film etching are still performed in wet benches with hot orthophosphoric acid. Several drawbacks from such process are presented with various ionic contaminations in high aspect ratio features. Moreover, a correlation is done between these contaminations and CMOS Image sensors device failure. Finally several process alternatives are given as solutions to replace the phosphoric wet benches.